Origin recognition complex subunit 6 (ORC6) is a key mediator of LPS-induced NFκB activation and the pro-inflammatory response - Zichen Xie; Haisu Lu; Jiayi Zheng; Jianfeng Song; Keyu Sun (Cell Communication and Signaling, 2024)
Abstract Lipopolysaccharide (LPS)-activated pro-inflammatory responses play a critical role in sepsis, a life-threatening condition. This study investigates the role of origin recognition complex subunit 6 (ORC6) in LPS responses in macrophages and monocytes. Silencing ORC6 using targeted shRNA significantly reduced LPS-induced expression and production of IL-1β (interleukin-1 beta), TNF-α (tumor necrosis factor alpha), and IL-6 (interleukin-6) in THP-1 human macrophages, peripheral blood mononuclear cells (PBMCs), and bone marrow-derived macrophages (BMDMs). Additionally, ORC6 knockout (KO) via the CRISPR/Cas9 method in THP-1 macrophages inhibited LPS-induced pro-inflammatory responses, while ectopic overexpression of ORC6 enhanced LPS-induced expression and production of pro-inflammatory cytokines. ORC6 is crucial for the activation of the nuclear factor kappa B (NFκB) signaling cascade in macrophages and monocytes. LPS-induced NFκB activation was largely inhibited by ORC6 silencing or KO, but potentiated following ORC6 overexpression. Mechanistically, ORC6 associated with nuclear p65 after LPS stimulation, an interaction necessary for NFκB activation. Overexpression of ORC6 did not recover the reduced pro-inflammatory response to LPS in THP-1 macrophages with silenced p65. Furthermore, the NFκB inhibitor BMS-345,541 nearly eliminated the pro-inflammatory response enhanced by ORC6 overexpression in response to LPS. Further studies revealed that ORC6 depletion inhibited NFκB activation induced by double-stranded RNA (dsRNA) and high mobility group box 1 (HMGB1) in THP-1 macrophages. In vivo experiments demonstrated that macrophage-specific knockdown of ORC6 protected mice from LPS-induced septic shock and inhibited LPS-stimulated production of IL-1β, TNF-α, and IL-6 in mouse serum. ORC6 silencing also inhibited LPS-induced NFκB activation in ex vivo cultured PBMCs following macrophage-specific knockdown of ORC6. These findings highlight ORC6 as a pivotal mediator in LPS-induced NFκB activation and the pro-inflammatory response in sepsis, suggesting that targeting ORC6 could be a novel therapeutic strategy for managing sepsis and related inflammatory conditions.